App-supported sleep coaching: implications for sleep duration and sleep quality - Gorovoy, Suzanne B.; Campbell, Rebecca L.; Fox, Rina S.; Grandner, Michael A. (Frontiers in Sleep, 2023)
OBJECTIVES: The present study evaluated whether completers of a 12-week app-supported sleep coaching program demonstrated improvements in sleep continuity, sleep duration, and reduced use of sleep aids. METHODS: Data were obtained from Sleep Reset, a 12-week app-supported sleep coaching program. 564 completers were included in the study. Pre-post changes for sleep latency (SL), wake after sleep onset (WASO), number of awakenings (NWAK), total sleep time (TST), sleep efficiency (SE%) and use of “sleep aids” were evaluated. To evaluate whether the program produced meaningful results, the proportion of participants who demonstrated reductions in SL, WASO, and NWAK, and increases in TST and SE% were examined. RESULTS: Mean SL was reduced by 11 minutes, mean WASO was reduced by 28 minutes, mean SE% increased by 6.6%, and mean TST increased by about 44 minutes. Of those who reported reliance on “sleep aids” during Week 1, 41% no longer used them by week 12. Those with low SE% at baseline demonstrated greater improvements in SL (16.2 vs 5.7mins), WASO (47.3 vs 7.2mins), SE% (11.2% vs 1.6%), and TST (65.3 vs 31.2mins). Those with ≤6 hours of sleep at baseline demonstrated greater improvements in WASO (36.8 vs 22.3mins), SE% (10.1% vs 4.3%), and TST (85.1 vs 25.5mins). CONCLUSIONS: An app-supported coaching intervention improved sleep duration and quality, with greater effects seen in those with lower sleep efficiency or sleep duration at baseline. An effective sleep coaching program that does not require a licensed health provider may provide a valuable resource for subclinical populations.